Lexical exhibitionism in D. Mitana ́s novel “Searching for a lost author” and J. Andrukhovych ́s novel “Moscowiade” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
At present, more and more attention is being paid to postmodernism and its individual sectors, for the phenomenon as a whole still does not have a unified definition and has not yet been examined in detail, which is the main reason why postmodern analysis is gaining in popularity. Moreover, national literatures such as the Slovak and Ukrainian postmodernism have not yet been subjected to a comparative analysis, and this fact irrefutably testifies to the need for such studies and their relevance. We tried to propose a new method of analysing postmodern texts, using the term “lexical exhibitionism”. The combination of sexual paraphilia and language creates the concept of “lexical exhibitionism”, which, thanks to Lacan, we do not understand as something of a sexual nature, but as a confirmation of human existence, by what is natural to it, or as an understanding of its own essence. To verify our theory in practice, we chose the works of important unique authors of Slovak and Ukrainian postmodernism, namely D. Mitana and his “Searching for the Lost Author”, and J. Andruchovych with the novel “Moscowiade”. Both authors very specifically represent the national stream of postmodern art, and are among the best postmodernists in their country. In addition, it is very interesting to compare the novels, because in both cases the main theme of the novel is sex. The analysis of the novels by Mitana and Andrukhovych in the context of “lexical exhibitionism” therefore allows us to conclude that, despite the significant socio-cultural differences between the two authors, both achieve relevant results associated, on the one hand, especially with overcoming sexual taboos, and on the other hand, with deep penetration to the foundations of human existence, filled with intractable contradictions and unmistakable loneliness, the tragic of which, paradoxically, denies exhibitionist outrage.
Keywords: D. Mitana; J. Andrukhovych; Slovak postmodernism; Ukrainian postmodernism; lexical exhibitionism